2009
DOI: 10.1051/0004-6361/200811021
|View full text |Cite
|
Sign up to set email alerts
|

Cluster and cluster galaxy evolution history from IR to X-ray observations of the young cluster RX J1257.2+4738 at z = 0.866

Abstract: Context. The cosmic time around the z ∼ 1 redshift range appears crucial in the cluster and galaxy evolution, since it is probably the epoch of the first mature galaxy clusters. Our knowledge of the properties of the galaxy populations in these clusters is limited because only a handful of z ∼ 1 clusters are presently known. Aims. In this framework, we report the discovery of a z ∼ 0.87 cluster and study its properties at various wavelengths. Methods. We gathered X-ray and optical data (imaging and spectroscop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
(46 reference statements)
1
13
1
Order By: Relevance
“…A.1 that a cut seems to appear at z ≥ 1 where infalling haloes are closer to the value of the main system mass. The position of this cut is also in good agreement with the expectations of Ulmer et al (2009), based on the typical relaxation time of a galaxy falling onto a typical cluster. This will obviously have to be confirmed on larger numerical simulations in the future given the relatively small number of massive structures present in the Millenium simulations.…”
Section: Appendix A: Infalling Activity On Clusters In the Millenniumsupporting
confidence: 87%
“…A.1 that a cut seems to appear at z ≥ 1 where infalling haloes are closer to the value of the main system mass. The position of this cut is also in good agreement with the expectations of Ulmer et al (2009), based on the typical relaxation time of a galaxy falling onto a typical cluster. This will obviously have to be confirmed on larger numerical simulations in the future given the relatively small number of massive structures present in the Millenium simulations.…”
Section: Appendix A: Infalling Activity On Clusters In the Millenniumsupporting
confidence: 87%
“…The final optical catalogue includes 1894 sources with completeness levels at 50% of 25.0, 24.3, 24.2, and 23.4 mag for g r i z , respectively. A final check of our photometry was performed against that from Ulmer et al (2009). To that end, we compared the distributions of galaxies in the i − z vs. i colour−magnitude diagram (a direct comparison of individual galaxies was not possible since the referred authors did not publish a source catalogue).…”
Section: Optical Broadband Imagingmentioning
confidence: 99%
“…The photometric cluster sample thus defined, along with a small spectroscopic sample (Ulmer et al 2009), yielded to a cluster sample of 271 + 21 = 292 galaxies. We merged this first cluster catalogue, using the nearest neighbour technique with a maximum error radii of 1.5 , with the [O ii]-emitters sample v LoS complete, and obtained a final cluster catalogue of 315 members.…”
Section: Multi-wavelength Cataloguementioning
confidence: 99%
See 1 more Smart Citation
“…Ulmer et al (2009) reported the discovery of the spectroscopically confirmed cluster at z = 0.866, on the basis of an extensive study including Chandra, XMM-Newton, Spitzer, Gemini, Subaru and ARC observations. They detected the diffuse emission of the cluster both in Chandra and XMM-Newton observations, and modelled that emission with an ellipse centered at RA(J2000) = 12h 57m 12.2s Dec(J2000) = +47…”
Section: Introductionmentioning
confidence: 99%